A macro-level investigation of transatlantic controlling shareholder's fiduciary duty - Anidjar, Leon (Cambridge University Press, 2021)
Legal systems around the world apply various strategies to mitigate agency costs between controlling and minority shareholders. A systematic review of the transnational law on the loyalty and care obligations of controlling shareholders reveals various doctrinal choices. This study aims to uncover the evolution of these choices by employing a law-in-context methodology. Accordingly, it seeks to explain the differences in governance selections by exploring the cultural, historical and socio-economic backgrounds of the particular legal systems in which organisations and decisions are embodied. I conduct a macro-level inquiry which focuses on the cultural environment and business history development to understand different doctrinal designs. In particular, I argue that those dissimilarities are a result of unique cultural-non-formal norms of corporate governance regarding the protection afforded to shareholders’ interests and they correspond to the historical development of the law of corporate groups across nations. As the macro-level investigation indicates, any initiative to globally converge corporate law and governance should be carried out with caution because it may distort the delicate normative equilibrium represented in a given jurisdiction.
Keywords: Global convergence of corporate governance and norms; Law of business groups; Cultural-non-formal norms of corporate governance; Controlling shareholders' loyalty and care obligations; 56 Ciencias Jurídicas y Derecho::5605 Derecho y legislación nacionales::5605.03 Derecho mercantil; ODS 16 - Paz, justicia e instituciones sólidas